Precise gene editing of pathogenic Lamin A mutations corrects cardiac disease - Xurde M. Caravia; Brian Hayashi; Hui Li; Peiheng Gan; Damir Alzhanov; Wei Tan; Kenian Chen; John R. McAnally; Lin Xu; Ning Liu; Eric N. Olson (Proceedings of the National Academy of Sciences, 2025)
Mutations in the Lamin A ( LMNA ) gene, which encodes the Lamin A and C proteins, cause severe human diseases collectively known as laminopathies. These conditions are often devastating and lack effective therapies. In this study, we developed precise base editing (BE) strategies targeting the human LMNA gene variants L35P and R249Q, which cause congenital muscular dystrophy (CMD) and dilated cardiomyopathy with conduction defects (DCM-CD), respectively. Induced pluripotent stem cell–derived cardiomyocytes (iPSC-CMs) carrying the R249Q mutation displayed nuclear aberrations, DNA damage, and abnormal Ca 2+ transients. Similarly, L35P iPSC-CMs exhibited abnormal contraction, DNA damage, and reduced Lamin A/C protein expression. We also generated “humanized” mouse models carrying these pathogenic human mutations. R249Q homozygous mice exhibited cardiac conduction abnormalities, cardiac arrhythmias, and premature death. Mice with the homozygous L35P mutation displayed severe muscle-wasting and reduced lifespan, while heterozygous L35P mice displayed DCM. We developed an adenine base editing (ABE) approach for correcting the R249Q mutation and a cytosine base editing (CBE) strategy for the L35P variant. Precise correction of these mutations in iPSC-CMs successfully rescued all of the in vitro abnormalities. Furthermore, delivery of the BE components using adeno-associated virus prevented the pathological phenotypes and extended longevity of mice carrying the LMNA L35P and the R249Q mutations. These results demonstrate the efficacy of ABE and CBE in correcting pathogenic LMNA mutations that cause cardiac disease, highlighting BE as a promising therapeutic approach for human laminopathies.